2019
DOI: 10.1257/pandp.20191104
|View full text |Cite
|
Sign up to set email alerts
|

Gender Bias and Temporal Effects in Standard Evaluations of Teaching

Abstract: This study investigates whether gender differences in SET vary over the course of a semester, particularly in response to feedback from the instructor. We survey principles of economics courses at multiple institutions three times during the semester to analyze whether the evaluations of male and female instructors change throughout the term, specifically after the first exam is returned. Results indicate a negative effect on evaluations for female instructors relative to male instructors associated with retur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Interestingly, early studies has shown that the post-course or semester evaluations in SET, to some extent, are significantly biased against female teachers. Also, many of the educational institutions rely exclusively on SET for decision-making purposes regarding the teachers (Boring, Ottoboni, & Stark, 2016;Whitney, Hayter, & Marshall, 2019). The findings on how the students evaluate their teachers' performance through the ECOA SET (see: the section on Data sampling and participants) revealed more comments for male teachers (52218) than for females (41072).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, early studies has shown that the post-course or semester evaluations in SET, to some extent, are significantly biased against female teachers. Also, many of the educational institutions rely exclusively on SET for decision-making purposes regarding the teachers (Boring, Ottoboni, & Stark, 2016;Whitney, Hayter, & Marshall, 2019). The findings on how the students evaluate their teachers' performance through the ECOA SET (see: the section on Data sampling and participants) revealed more comments for male teachers (52218) than for females (41072).…”
Section: Discussionmentioning
confidence: 99%
“…Their study examines the application of SETs in principles of economics courses at multiple institutions on three separate occasions during the semester in order to determine whether the evaluations of male and female instructors change throughout an academic term, specifically after the first exam is returned. Tests presented by Buser et al [17] point toward a negative effect on evaluations for female instructors relative to male instructors associated with returning grades, thus highlighting the importance of temporal effects (related to gender) in the application of SETs.…”
Section: Gender and Other Demographic Effects In Setsmentioning
confidence: 98%
“…As one moves toward academic disciplines wherein female instructors are more common, the ratings of female instructors by female students rise. Lastly, in light of earlier findings of a gender effect in SETs, Buser et al [17] investigate whether gender differences in SETs vary over the course of a semester. Their study examines the application of SETs in principles of economics courses at multiple institutions on three separate occasions during the semester in order to determine whether the evaluations of male and female instructors change throughout an academic term, specifically after the first exam is returned.…”
Section: Gender and Other Demographic Effects In Setsmentioning
confidence: 99%
“…The authors note that there still exists some issues and challenges in relation to the pedagogical transformations, hand-inhand with the impact of the digital teaching and acceleration of the new innovative models and practices form learning, that can only be achieved through a culture of educational innovation and conceptual understanding of how the effectiveness of the learning processes and outcomes are assessed [18], [76], [81], [113], [114]. A lot of higher educational institutions rely exclusively on SET evaluations for assessment of the teachers' performance and learning outcomes of the students [53], [115], [116], and there are also evidence in the literature that information (educational datasets) about the teaching and learning processes (which are stored at an unprecedented rate in the databases of the different institutions) can be used to understand and drive the educational systems forward [8], [27], [49], [89], [117], [118]. VOLUME 11, 2023 In triangulation with the method and objectives of this current study, educational organizations such as The Association for Institutional Research (AIR) [119] and The Professional and Organizational Development Network in Higher Education (POD) [120] are already pioneering several themes that are focused on students/learning assessment, institutional effectiveness and use of (educational) data for informed decision-making and support of the educators or educational processes to include (i) Assessment and Evaluation initiatives that are focused on research and methods that are both externally or internally driven from the institutional perspective for planning, accreditation, amongst others, in pursuit of improved and equitable student' and institutional success (ii) Data and Technology that features the technical and ethical creation/manipulation of data and structuring through appropriate analytic tools for decision making, predictive models, and machine learning (iii) Institutional Effectiveness which constitute of student-focused paradigm that explores the roles of information retrieval (IR), information extraction (IE), and Assessment in leading institutional data strategies and strategic planning for improvement of the students' success (iv) Use of Data that proves important for improved student success with attention to institutional and student contexts, [119], [120] etc., as uncovered in this study.…”
Section: A Implications Of This Studymentioning
confidence: 99%